Measuring the Transport Patterns of Those Living in Deprived Areas in Dublin, Ireland - CAULFIELD, BRIAN (My University, 2012)
This paper examines the relationship between social deprivation and travel patterns . Many studies ha ve examined the relationsh ip between deprivation and travel patterns , but few have compared those in the most disadvantaged areas with those living in the most affluent areas. This study examines the impact that deprivation has upon individuals’ trip patte rns , in Dublin, using 2006 Census of I reland data. A number of maps were created to determine the patterns of deprived areas in the city relative to a number of trip chara cteristics. A multinomial logistic regression model wa s estimated in this study to determine how the level of deprivation impacts upon a number of characteristics such as mode choice, annual emissions, cost of transport and car ownership. The main findings of this study are that those individuals living in deprived areas in Dublin are m ore likely to use sustainable modes of transport compared to individuals living in the more affluent areas of the city.
91st Annual Meeting of the Transportation Research Board
PUBLISHED
Washington, D.C
Keywords: Transport; Smart & Sustainable Planet